Performance changes in NBA basketball players vary in starters vs. nonstarters over a competitive season - Gonzales, A. M.; Hoffman, J. R.; Rogowski, J. P.; Burgos, W.; Manalo, E.; Weise, K.; Fragala, M. S.; Stout, J. R. (The Journal of Strength and Conditioning Research, 2013)
The purpose of this study was to compare starters (S) with nonstarters (NS), on their ability to maintain strength, power, and quickness during a competitive National Basketball Association (NBA) season. Twelve NBA players were assessed at the beginning and end of the competitive season. However, because of trades and injury, only 7 (S = 4, NS = 3) players (28.2 ± 3.4 years; 200.9 ± 9.4 cm; 104.7 ± 13.9 kg; 7.2 ± 1.9% body fat) participated in both testing sessions and underwent analysis. Anthropometric performance (repetitive vertical jump power [VJP], squat power [SQT power], and reaction time) and subjective feelings of energy, focus, alertness, and fatigue were recorded during each testing session. Results were interpreted using magnitude-based statistics to make inferences on true differences between starters and nonstarters using the unequal variances t-statistic. Starters played an average of 27.8 ± 6.9 minutes per game and nonstarters played an average of 11.3 ± 7.0 minutes per game. During the course of the season, changes in VJP indicated that starters were likely to increase VJP ([INCREMENT] = 77.3 ± 78.1 W) compared to nonstarters ([INCREMENT] = -160.0 ± 151.0 W). There also appeared to be a possible beneficial effect on maintaining reaction time in starters ([INCREMENT] = 0.005 ± 0.074 seconds) compared with nonstarters ([INCREMENT] = 0.047 ± 0.073 seconds). In addition, no clear differences in dSQT power were seen between starters ([INCREMENT] = 110.8 ± 141.4 W) and nonstarters ([INCREMENT] = 143.5 ± 24.7 W). Changes in subjective feelings of energy indicated that starters were very likely to maintain their energy over the course of a season. It also appeared possible that starters were able to have a more positive response to subjective measures of fatigue and alertness than nonstarters, with only trivial differences between starters and nonstarters in regards to maintaining focus. Results of this study suggest that NBA players may enhance lower-body power, repetitive jump ability, and reaction during a competitive season, which appear to be enhanced with the stimulus of playing time.